2015
DOI: 10.1111/tri.12508
|View full text |Cite
|
Sign up to set email alerts
|

Ureteric reconstruction for the management of transplant ureteric stricture: a decade of experience from a single centre

Abstract: SummaryThis study was conducted to review the outcomes of patients who had undergone surgical repair of a ureteric stricture following renal transplantation. All patients who developed a ureteric stricture and underwent ureteric reconstruction following renal transplantation, between December 2003 and November 2013, were reviewed. One thousand five hundred and sixty renal transplants were performed during the study period. Forty patients required surgical repair of a ureteric stricture (2.5%, 25 male, median a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
13
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 26 publications
2
13
0
Order By: Relevance
“…However, Pike and associates stated that this method was not appropriate as dissection of the native ureter is often difficult in the presence of a transplanted kidney and the integrity of a native ureter is mostly not known or investigated. 6 Here, however, we showed that assessment of the integrity of the ureters can be done properly by urologists using urethrocystoscopy during the preoperative period. Moreover, this method provides the opportunity to directly measure the length of the rest of the ureter and to place into the lumen of the ureter one of the stents to make it easer to find the ureter during the operation.…”
Section: Discussionmentioning
confidence: 77%
See 3 more Smart Citations
“…However, Pike and associates stated that this method was not appropriate as dissection of the native ureter is often difficult in the presence of a transplanted kidney and the integrity of a native ureter is mostly not known or investigated. 6 Here, however, we showed that assessment of the integrity of the ureters can be done properly by urologists using urethrocystoscopy during the preoperative period. Moreover, this method provides the opportunity to directly measure the length of the rest of the ureter and to place into the lumen of the ureter one of the stents to make it easer to find the ureter during the operation.…”
Section: Discussionmentioning
confidence: 77%
“…[3][4][5][6] The optimal surgical approach for reconstruction of such ureteric stenosis depends on the stricture's section. Because common surgical approaches or a fourth transplant are not always optimal, as for our present complicated case, an alternative approach for urinary tract reconstruction by anastomosis to the contralateral native ureter was developed.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…When techniques for reconstruction of the proximal ureter in humans are being considered, there are several guiding surgical principles including techniques that allow for a wide, tension free and water tight anastomoses; the preservation of blood supply; and complete excision of the underlying pathology to prevent stricture recurrence . Surgical techniques currently performed in man include ureteroureterostomy, transureteroureterostomy, downward nephropexy, ureterocalicostomy, Boari bladder flap, psoas hitch, bowel interposition, pyeloplasty, renal autotransplantation, and nephrectomy . The technique chosen often depends on the location of the obstruction as well as its length.…”
Section: Introductionmentioning
confidence: 99%